Application of Prestressed Pipe Pile in Foundation Treatment - Liu, Shiying (Journal of Theory and Practice of Engineering Science, 2023)
Our terrain is very complex, in some coastal areas, soft soil coverage is very high, due to the geological changes, all the physical properties of soft soil will appear great changes. Now it seems that prestressed pipeline technology can effectively prevent this problem, the essence of pipeline pretreatment foundation stack is to rely on its own strength, enhance the bearing capacity of the whole foundation. Because of the fast construction speed, the effect of improving the bearing capacity of the foundation is remarkable, which brings remarkable economic benefits for the construction project.